Emotional Intelligence: Association With Negative Emotions and job Performance in University Teachers - Castro-Paniagua, William (2023)
Objective. Our aim was to determine the relationship between emotional intelligence, negative emotions, and job performance, and the level of these variables in university teaching staff. Method. It is a basic, descriptive, simple correlational transactional research; the complete Baron ICE:NA emotional intelligence test, the inventory of emotional regulation skills and the job performance questionnaire were used with a sample of 75 teachers, average age 45 years, in two universities in Peru. Frequencies and Pearson’s correlation were used in the analysis. Conclusions. The results show a positive association between emotional intelligence and job performance; on the other hand, emotional intelligence and job performance are negatively associated with negative emotions. In addition, the level found in emotional intelligence is balanced, regular in negative emotions and good for job performance. The study determines that, if negative emotions are regulated, it would improve the emotional intelligence and job performance of teachers.